Renewable Energy and Health: Bibliometric Review of Non-Medical Research - Ihor Vakulenko; Hlib Lieonov (Health Economics and Management Review)
Renewable energy has been a top topic for research for decades. Studying this issue is essential based on the need to find effective ways to replace fossil fuels with renewable ones. Climate change is the driver of the transition to renewable energy. And suppose the reason for the need to switch to renewable energy is clear to everyone. The methods provoke significant discussions, which have not stopped for a moment since the beginning of research on this topic. The economic aspect of replacing fossil fuels with renewables is paramount to developing effective business models that allow for the rapid replication of good practices. To this end, various mechanisms of state support and the formation of market incentives for investors were tested. However, the issue of the cost-effectiveness of fossil fuel substitution remains problematic. The issue of energy substitution cannot be considered solely in the economic sphere. The reason for this is the significant number of hidden or indirect effects that are difficult to evaluate. However, this needs to be done to understand renewable energy development's true efficiency and importance. The global impact of large-scale renewable energy technologies is to reduce climate change loss. One of the most important aspects to study and quantify is the impact of energy and public health. It is well known that fossil fuels, being environmentally dirty, harm the human habitat. Declining environmental quality directly affects the number of diseases and life expectancy. Many studies have focused on approaches and quantifying economic losses due to environmental degradation. However, the question of how renewable energy reduces these losses remains poorly studied. Most research on the impact of energy on the environment focuses on reducing emissions. Such studies are extremely valuable but do not allow us to conclude the direct effects of fossil fuel substitution on renewable energy on human life and health and quantify this impact accordingly. This article focuses on the current state of research on the impact of renewable energy on the lives and health of the population and the costs associated with it. Based on available research, the article reviews the scientific developments on this topic in publications, mainly non-medical profiles.